The complete encyclopedia of horse racing : the illustrated guide to the world of the thoroughbred - Mooney, Bill. frey50; Ennor, George (London : Carlton, 2009)
An authoritative and comprehensive illustrated work of reference, which tells the story of the "sport of kings" from its earliest inception to the present day.
Introduction -- The early history of horse racing -- Horse racing around the world -- The major races -- Legendary horses -- A-Z of famous horses -- Legendary jockeys -- A-Z of racing greats -- Gambling -- Scandals and controversies -- Trivia and records -- Chronology -- Index.
Previous ed.: 2007.
Includes index.
Keywords: Horse racing